Is It Time to Review Guidelines for ETT Positioning in the NICU? SCEPTIC—Survey of Challenges Encountered in Placement of Endotracheal Tubes in Canadian NICUs. (19th January 2016) - Sakhuja, Pankaj; Finelli, Michael; Hawes, Judy; Whyte, Hilary
Abstract : Objectives . To examine current opinions and practices regarding endotracheal tube placement across several Canadian Neonatal Intensive Care Units. Design . Clinical directors from Canadian Neonatal Network affiliated NICUs and Neonatal-Perinatal Programs across Canada were invited via email to participate in and disseminate the online survey to staff neonatologists, neonatal fellows, respiratory therapists, and nurse practitioners. Result . There is wide variability in the beliefs and practices related to ETT placement. The majority use "weight +6" formula and "aim to black line" on ETT at vocal cords to estimate the depth of an oral ETT and reported estimation as challenging in ELBW infants. The majority agreed that mid-trachea is an ideal ETT tip position; however their preferred position on chest X-ray varied. Many believe that ETT positioning could be improved with more precise ETT markings. Conclusion . Further research should focus on developing more effective guidelines for ETT tip placement in the ELBW infants.